Fracture phenomena in micro‐ and nano‐layered polycarbonate/poly(vinylidene fluoride‐co‐hexafluoropropylene) films under electric field for high energy density capacitors. Issue 4 (24th September 2013) - Zhou, Zheng; Mackey, Matt; Yin, Kezhen; Zhu, Lei; Schuele, Donald; Flandin, Lionel; Baer, Eric
ABSTRACT The long‐term dielectric lifetime properties of multilayered polycarbonate/poly(vinylidene fluoride‐co‐hexafluoropropylene) [PC/P(VDF‐HFP)] films were measured as a function of the layer thickness. An optimum layer thickness of 160 nm was determined with the longest dielectric lifetime. The morphology of the damaged sites after dielectric breakdown was examined using scanning electron microscope. Acoustic emission detection system was coupled with the dielectric setup to correlate fracture events and dielectric breakdown to thereby elucidate the mechanisms of the enhancements in dielectric lifetime properties. Two types of acoustic signals were always observed during the breakdown process for multilayered films. The high‐amplitude signals were attributed to the formation of breakdown pinholes caused by the primary discharge from top to bottom electrode. The subsequent low‐amplitude signals were attributed to internal discharges that could further damage the film. The total number of acoustic hits, in particular, low‐amplitude hits, increased with decreasing layer thickness, indicating more internal discharges occurred along the layered interface. It was concluded that the breakdown event initiated at a defect initiated "hotspot" formed because of internal pressure buildup. The film was punctured when the pressure buildup inside the film overcame the mechanical strength of the film. More number of PC layers and layer interfaces were desirable to slow down and divert the damage propagation through the film thickness direction. The crazes in P(VDF‐HFP) can, however, easily propagate across PC layers with less than 160 nm layer thickness. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39877.